The UPF1 interactome reveals interaction networks between RNA degradation and translation repression factors in Arabidopsis. (1st August 2018) - Chicois, Clara; Scheer, Hélène; Garcia, Shahïnez; Zuber, Hélène; Mutterer, Jérôme; Chicher, Johana; Hammann, Philippe; Gagliardi, Dominique; Garcia, Damien
Summary: The RNA helicase UP‐FRAMESHIFT (UPF1) is a key factor of nonsense‐mediated decay (NMD), a mRNA decay pathway involved in RNA quality control and in the fine‐tuning of gene expression. UPF1 recruits UPF2 and UPF3 to constitute the NMD core complex, which is conserved across eukaryotes. No other components of UPF1‐containing ribonucleoproteins (RNPs) are known in plants, despite its key role in regulating gene expression. Here, we report the identification of a large set of proteins that co‐purify with the Arabidopsis UPF1, either in an RNA‐dependent or RNA‐independent manner. We found that like UPF1, several of its co‐purifying proteins have a dual localization in the cytosol and in P‐bodies, which are dynamic structures formed by the condensation of translationally repressed mRNPs. Interestingly, more than half of the proteins of the UPF1 interactome also co‐purify with DCP5, a conserved translation repressor also involved in P‐body formation. We identified a terminal nucleotidyltransferase, ribonucleases and several RNA helicases among the most significantly enriched proteins co‐purifying with both UPF1 and DCP5. Among these, RNA helicases are the homologs of DDX6/Dhh1, known as translation repressors in humans and yeast, respectively. Overall, this study reports a large set of proteins associated with the Arabidopsis UPF1 and DCP5, two components of P‐bodies, and reveals an extensive interaction network between RNA degradation and translation repression factors. Using this resource, we identified five hitherto unknown components of P‐bodies in plants, pointing out the value of this dataset for the identification of proteins potentially involved in translation repression and/or RNA degradation. Significance Statement: Nonsense‐mediated decay is an essential process involved in development, hormone and pathogen response through the repression of gene expression by the RNA helicase UPF1. Despite its major functions, this process is still poorly understood in plants compared with mammals. By an unbiased strategy we identified protein partners of UPF1, and discovered unappreciated associations between factors involved in RNA decay and translation regulation, allowing the identification of hitherto unknown P‐body components with potential function in these processes.